MiR-100-5p Promotes Epidermal Stem Cell Proliferation through Targeting MTMR3 to Activate PIP3/AKT and ERK Signaling Pathways. (21st August 2022) - Liu, Zhe; Yang, Yuan; Ju, Jihui; Zhang, Guangliang; Zhang, Ping; Ji, Pengxiang; Jin, Qianheng; Cao, Gaobiao; Zuo, Rui; Wang, Hongyu; Yu, Chenghao; Zhang, Zhiqiang; et al.
Abstract : Skin epidermal stem cells (EpSCs) play a critical role in wound healing and are ideal seed cells for skin tissue engineering. Exosomes from human adipose-derived stem cells (ADSC-Exos) promote human EpSC proliferation, but the underlying mechanism remains unclear. Here, we investigated the effect of miR-100-5p, one of the most abundant miRNAs in ADSC-Exos, on the proliferation of human EpSCs and explored the mechanisms involved. MTT and BrdU incorporation assays showed that miR-100-5p mimic transfection promoted EpSC proliferation in a time-dependent manner. Cell cycle analysis showed that miR-100-5p mimic transfection significantly decreased the percentage of cells in the G1 phase and increased the percentage of cells in the G2/M phase. Myotubularin-related protein 3 (MTMR3), a lipid phosphatase, was identified as a direct target of miR-100-5p. Knockdown of MTMR3 in EpSCs by RNA interference significantly enhanced cell proliferation, decreased the percentage of cells in the G1 phase and increased the percentage of cells in the S phase. Overexpression of MTMR3 reversed the proproliferative effect of miR-100-5p on EpSCs, indicating that miR-100-5p promoted EpSC proliferation by downregulating MTMR3. Mechanistic studies showed that transfection of EpSCs with miR-100-5p mimics elevated the intracellular PIP3 level, induced AKT and ERK phosphorylation, and upregulated cyclin D1, E1, and A2 expression, which could be attenuated by MTMR3 overexpression. Consistently, intradermal injection of ADSC-Exos or miR-100-5p-enriched ADSC-Exos into cultured human skin tissues significantly reduced MTMR3 expression and increased the thickness of the epidermis and the number of EpSCs in the basal layer of the epidermis. The aforementioned effect of miR-100-5p-enriched ADSC-Exos was stronger than that of ADSC-Exos and was reversed by MTMR3 overexpression. Collectively, our findings indicate that miR-100-5p promotes EpSC proliferation through MTMR3-mediated elevation of PIP3 and activation of AKT and ERK. miR-100-5p-enriched ADSC-Exos can be used to treat skin wound and expand EpSCs for generating epidermal autografts and engineered skin equivalents.